Towards a Sound New Zealand Intellectual Property Law - Frankel, Susy (Victoria University of Wellington Law Review, 2001)
This article discusses aspects of New Zealand's intellectual property law and policy. The author examines New Zealand's existing laws and international obligations. The author proposes that New Zealand develop a sound law of intellectual property that honours the Treaty of Waitangi and is of benefit to New Zealanders. She considers a number of aspects of New Zealand's international obligations and demonstrates how New Zealand can develop laws that assist New Zealanders in the fields of science and technology, business and the arts and not contravene our international commitments. The article concludes that New Zealand's intellectual property law should be founded on policies that enhance the development and use of knowledge based assets for New Zealanders.